Growth, survival and bacterial load of sex-reversed tilapia hybrid (Oreochromis niloticus x oreochromis mossabicus) cultured in seawater netcages at various stocking densities - Salvador, Ronelie Chato (College of Fisheries, University of the Philippines in the Visayas, 1992)
The growth performance and survival of tilapia hybrid (Oreochromisniloticus x Oreochromismossambicus) in the marine environment were compared at three stocking densities (50, 100 and 200 fish/m3). The bacterial population of the cultured stocks and seawater was also investigated to obtain baseline information on seacage management procedures, particularly disease prevention and control. The fry hybrids were spawned in freshwater, sex-reversed for three weeks at 5-15 ppt, nursed for about one month in tanks at 15-25 ppt, and reared in 1 m3 floating netcages for 131 days at 34-38 ppt. Specific growth rate, condition factor, feed conversion ratio, survival, fish yield and bacterial load were determined at each stocking density. No significant difference in specific growth rates, condition factors, feed conversion ratios and survival was observed between stocking densities. Difference in fish yield was highly significant between 100 and 200 fish/m3. Specific growth rates (2.78% - 2.98%) and condition factors (1.78% - 1.85%) were low but feed conversion ratios (2.78 -3. 22) were high. This result was correlated to high energy demand of osmoregulation, growth and aggression at high salinity. Bacteria isolated from liver samples and rearing seawater were Pseudominas sp. (35.71%), Flavobacterium sp. (28.58%), Vibrio sp. (21.43%), Alcaligenes sp. (7.14%) and Acinetobacter sp. (7.14%). No correlation between bacterial load of rearing seawater, fish biomass and water physic-chemical parameters was observed. Studies on feeding requirements in seawater and the growth response of tilapia hybrid at seacage biomass higher than 200 fish/m3 are recommended.